The relationships among Taiwanese youth’s polychronicity, multitasking behavior and perceived learning performance in online learning - Luo, Yi Fang; Kang, Seokmin; Yang, Shu Ching; Lu, Chia Mei (Frontiers in Psychology, 2023)
Background: The advancement of digital technology implies the importance of polychronic learning. Since polychronicity is not equivalent to multitasking behavior, they need to be considered separately. However, less research has been explored on how polychronicity is related to multitasking behavior in the educational field. Objective: To explore the relationships among polychronicity, multitasking behavior and learning performance (including knowledge acquisition and learning satisfaction) in an online learning environment. Methods: The relationship among variables was analyzed from 865 responses obtained from a questionnaire survey, and independent samples t tests and SEM analysis were used to examine the research hypotheses. Results: College students showed a higher frequency of multitasking behavior, time tangibility and scheduling preference, and learning satisfaction in multitasking online learning environments than high school students. Additionally, college students were different from high school students on the paths of involvement with people to multitasking behavior (Δχ^2 = 5.42, p = .02) and scheduling preference to learning satisfaction (Δχ^2 = 9.54, p = .002). Conclusions: The relationship among polychronicity, multitasking behavior and perceived learning performance in an online learning environment varies by student educational stage.